Genital ulcers in women: clinical, microbiologic and histopathologic characteristics - Gomes,Christiane Maria Moreira (2007)
Female genital ulcer is a disease that affects a large number of women, and its etiologic diagnosis can be difficult. The disease may increase the risk of acquiring HIV. Genital ulcer may be present in sexually transmitted diseases (STD) - syphilis, chancroid, genital herpes, donovanosis, lymphogranuloma venereum and other non-STD disorders (NSTD) - Behçet's syndrome, pemphigus, Crohn's disease, erosive lichen planus and others. This study evaluated the clinical-histopathologic-microbiologic characteristics of female genital ulcers. A cross-sectional descriptive prospective study was conducted during a six-month period to investigate the first 53 women without a definitive diagnosis, seeking medical care for genital ulcers at a genital infections outpatient facility in a university hospital. A detailed and specific history was taken, followed by a dermatologic and gynecologic examination. In addition to collecting material from the lesions for microbiologic study, a biopsy of the ulcer was performed for histopathologic investigation. The average age of the patients was 32.7 years, 56.6% had junior high school education and higher education. The most frequent etiology was herpetic lesion, followed by auto-immune ulcers. At the time of their first consultation, around 60% of the women were using inadequate medication that was inconsistent with the final diagnosis. Histologic diagnosis was conclusive in only 26.4% of the patients (14/53). Cure was obtained in 99% of the cases after proper therapy. The female genital ulcers studied were equally distributed between sexually transmitted and non-sexually transmitted causes. Herpes was the most frequent type of genital ulcer, affecting women indiscriminately, mostly between the ages of 20 and 40 years. The etiologic diagnosis of herpetic ulcers is difficult to make even when various diagnostic methods are applied. It is imperative that NSTD should be included in the differential diagnoses of female genital ulcers. The histopathologic exam is not a diagnostic tool in the majority of cases and should not be considered the gold standard test, being of little value in cases of NSTD and STD ulcers.